2013
DOI: 10.1111/bju.12381
|View full text |Cite
|
Sign up to set email alerts
|

The role of magnetic resonance imaging in the diagnosis and management of prostate cancer

Abstract: Background• The diagnosis of prostate cancer has long been plagued by the absence of an imaging tool that reliably detects and localises significant tumours. Recent evidence suggests that multi-parametric MRI could improve the accuracy of diagnostic assessment in prostate cancer. This review serves as a background to a recent USANZ position statement. It aims to provide an overview of MRI techniques and to critically review the published literature on the clinical application of MRI in prostate cancer. Technic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 131 publications
1
101
0
2
Order By: Relevance
“…In previous reports, the detection rate of PCa in biopsed PI-RADS 3 lesions has shown a significantly high variability, ranging from 5% to 26%. [23][24][25] PCa is often a solid lesion with a defined three dimensional shape. Consequently a major diagnostic potential of MRI lesion volume for suspicious PCa might be proposed to identify PI-RADS 3 lesions to be biopsied.…”
mentioning
confidence: 99%
“…In previous reports, the detection rate of PCa in biopsed PI-RADS 3 lesions has shown a significantly high variability, ranging from 5% to 26%. [23][24][25] PCa is often a solid lesion with a defined three dimensional shape. Consequently a major diagnostic potential of MRI lesion volume for suspicious PCa might be proposed to identify PI-RADS 3 lesions to be biopsied.…”
mentioning
confidence: 99%
“…The rapid optimization of MRI technology has led to functional imaging using diffusion-weighted, dynamic contrast-enhanced and spectroscopic imaging. Combining these functional techniques with the traditional (T1/T2) techniques (parameters) resulted in a multi parametric MRI (mpMRI) which has led to improved diagnostic performance for the detection of high grade lesions [19].…”
Section: Improvements In Mrimentioning
confidence: 99%
“…11,12 Recently, multiparametric magnetic resonance imaging (mpMRI), including diffusion-weighted imaging (DWI), has emerged as an important modality in prostate cancer diagnosis. [13][14][15] Several studies have identified the role of the apparent diffusion coefficient (ADC) value, obtained from DWI sequences, as a novel tool that may improve the diagnosis and management of prostatic cancer. These studies focused on the association between ADC value and GS.…”
Section: Introductionmentioning
confidence: 99%